The handbook of media education research - Frau-Meigs, Divina; Kotilainen, Sirkku; Pathak-Shelat, Manisha; Hoechsmann, Michael; Poyntz, Stuart R. (John Wiley & Sons, Inc., 2021)
"The challenge for researchers is not only to explain the problems, but also to communicate with the people in power so that research findings will make a difference. They need to dare to engage in debates on democracy, social change, human rights, freedom of expression - and the role of media education in relation to these fundamental values. In such a context, the Handbook on Media Education Research makes a very important contribution to increasing our knowledge and understanding of media education on a global basis. Nearly 40 well-known, international researchers formulate important themes, approaches and valuable insights into the dynamic and evolving field of media education research in the digital age. The book provides a fruitful framework for discussing critical issues from different perspectives: theoretical, methodological and practical; educational, pedagogic and political; local and global. The goal stated in the introductory chapter to present a "historically informed and future-oriented work" is very well achieved through this broad and in-depth picture of the state of media education research around the world. The Handbook on Media Education Research offers researchers, decision-makers, teachers and practitioners the knowledge and experience needed for media education to be effective from a civic and long-term perspective"- Resumé vydavatele
Keywords: masmédia; studium a výuka; mediální gramotnost; mediální výchova a vzdělávání; mass media; study and teaching; media literacy; media education; elektronické knihy; kolektivní monografie; electronic books; collective monographs